POTENSI EKSTRAK AIR DAUN ALPUKAT(Persea americana M.) SEBAGAI DIURETIKPADA TIKUS PUTIH JANTAN - Triyani Sumiati; Ferry Effendi; Muhamad Sofyan Iskandar (Jurnal Farmamedika (Pharmamedika Journal), 2016)
Diuretics is a substance that can stimulate of urine output. The content of flavonoid compunds contained in water extracts of avocado leaves have a diuretic activity. Testing is done withgiving a water extract of avocado leaves per oral to 30 male rats strain (Sparague-Dawley) with weight 200 grams were divided into 6 groups. Frequency of urination with water extract of avocado leaves 5 % , 10 % , 15 % and 20 % respectively which is 2 , 5 , 9 and 20 times with observation for 3 hours. Furosemide tablets urination frequency was 25 times over 3 hours. The result showed that the water extract of avocado leaves 20% have diuretic activity is equivalent to Furosemide tablets at a dose of 7.2 mg / 200 mg BB in male rats.